2011
DOI: 10.1029/2011gc003738
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the crust beneath the Afar triple junction: Evidence from receiver functions

Abstract: [1] The Afar depression is an ideal locale to study the role of extension and magmatism as rifting progresses to seafloor spreading. Here we present receiver function results from new and legacy experiments. Crustal thickness ranges from ∼45 km beneath the highlands to ∼16 km beneath an incipient oceanic spreading center in northern Afar. The crust beneath Afar has a thickness of 20-26 km outside the currently active rift segments and thins northward. It is bounded by thick crust beneath the highlands of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
338
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 171 publications
(386 citation statements)
references
References 94 publications
(255 reference statements)
46
338
2
Order By: Relevance
“…Discussion has often focussed on whether the crust is completely new oceanic crust, or whether it is stretched and thinned continental crust, heavily intruded by magma (transitional crust). Constraints on crustal structure primarily come from wide-angle seismic studies (Berckhemer et al, 1975;Maguire et al, 2006;Makris and Ginzburg, 1987;Prodehl et al, 1997), teleseismic receiver function studies (Ayele et al, 2004;Dugda et al, 2005;Hammond et al, 2011;Stuart et al, 2006), and from gravity analysis (Redfield et al, 2003;Tessema and Antoine, 2004;Tiberi et al, 2005). Results achieved using these different methods are broadly consistent (e.g., Fishwick and Bastow, 2011).…”
Section: Crustal Structurementioning
confidence: 68%
See 1 more Smart Citation
“…Discussion has often focussed on whether the crust is completely new oceanic crust, or whether it is stretched and thinned continental crust, heavily intruded by magma (transitional crust). Constraints on crustal structure primarily come from wide-angle seismic studies (Berckhemer et al, 1975;Maguire et al, 2006;Makris and Ginzburg, 1987;Prodehl et al, 1997), teleseismic receiver function studies (Ayele et al, 2004;Dugda et al, 2005;Hammond et al, 2011;Stuart et al, 2006), and from gravity analysis (Redfield et al, 2003;Tessema and Antoine, 2004;Tiberi et al, 2005). Results achieved using these different methods are broadly consistent (e.g., Fishwick and Bastow, 2011).…”
Section: Crustal Structurementioning
confidence: 68%
“…The structure and composition of the crust beneath Afar have been the subject of much debate during the last~35 years (e.g., Berckhemer et al, 1975;Hammond et al, 2011;Makris and Ginzburg, 1987;Mohr, 1970Mohr, , 1989. Discussion has often focussed on whether the crust is completely new oceanic crust, or whether it is stretched and thinned continental crust, heavily intruded by magma (transitional crust).…”
Section: Crustal Structurementioning
confidence: 99%
“…More recent studies of the Afar region and Ethiopian Rift Valley have revealed physical and chemical heterogeneity [e.g., (Ebinger et al 2010;Ebinger and Sleep 1998;Furman et al 2006;Keir et al 2011;Pik et al 2008Pik et al , 2006 Rooney et al 2012a]; Hammond et al (2011) showed that there is a considerable variation in Moho depth across Afar, even within the central rift area. Their study area does not quite reach the Bidu Massif, but points to a crust thickness of about 20 km in the region of the Danakil Horst (Fig.…”
Section: Regional Backgroundmentioning
confidence: 99%
“…Despite the logistical challenges of carrying out fieldwork in Afar, several decades of research underpin our current understanding of the regional volcanism and rifting (Ayele et al 2007(Ayele et al , 2009; Barberi et al 1974a, b;Ferguson et al 2010;Field et al 2012aField et al , b, 2013Hammond et al 2013Hammond et al , 2011Keir et al 2013Keir et al , 2011Lahitte et al 2003). Expeditions in the 1970s documented Afar volcanism at reconnaissance scale (Barberi et al 1974a(Barberi et al , b, 1970Civetta et al 1975).…”
Section: Regional Backgroundmentioning
confidence: 99%
See 1 more Smart Citation